Mobility for learners and staff - higher education students and staff mobility inter-institutional agreement 2017-2018-2020/2021 between programme countries – Università degli Studi di Firenze and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2017)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Economics; psychology; law; International relations; Architecture and building; Architecture and town planning.